Characteristics of Physical Activity in Early Childhood Through the Application of Pedagogical Strategies in Outdoor Environments - GERASIMOVICIENE, Vilija; KETURAKIENE, Ilona (International Journal of Holistic Health, Sports and Recreation, 2025)
This study aim to investigate the development of outdoor physical activity (PA) and pedagogical strategies for children aged 1.5 to 3 years. The study used purposive sampling, deliberately selecting a group of six informants, pre-school teachers working with children aged 1.5 to 3 years, through focus group design. The sample for qualitative study was flexible and based on the principle of data saturation, interviews were carried out until new information became available. Key issues identified included following questions: do children aged 1.5 to 3 years spend sufficient time outdoors in pre-schools? Are the conditions for children's PA in outdoor environments of pre-schools adequate? In response, pre-school teachers employed various strategies such as (in)formally assessing children's progress and planning new activities constantly strive for the goals of children's comprehensive education. Pedagogical effects for children PA revealed through various activities which are characterized by playful features, various movement places, active games, thematic weeks. An analysis of the impact of outdoor environments on the PA of children aged 1.5 to 3 years the findings revealed a direct influence on the expression of PA. The outdoor environment encourages a variety of movements, enhances motor skill development, fosters healthy PA habits, and provides opportunities for exploration, creative engagement, and social interaction. In requirements for outdoor environments, teachers strive to ensure they are adapted to the needs of young children: safe, stimulating, flexible, dynamic, and spacious enough to support free movement, with a variety of age-appropriate and safe equipment.